Immersion, presence, and episodic memory in virtual reality environments. Issue 8 (14th September 2021) - Smith, S. Adam; Mulligan, Neil W.
ABSTRACT: Although virtual reality (VR) represents a promising tool for psychological research, much remains unknown about how properties of VR environments affect episodic memory. Two closely related characteristics of VR are immersion (i.e., the objective degree to which VR naturalistically portrays a real-world environment) and presence (i.e., the subjective sense of being "mentally transported" to the virtual world). Although some research has demonstrated benefits of increased immersion on VR-based learning, it is uncertain how broadly and consistently this benefit extends to individual components of immersion. Moreover, it is unclear whether presence may mediate the effect of immersion on memory. Three experiments assessed how presence and memory were affected by three manipulations of immersion: field of view, unimodal (visual only) vs. bimodal (audiovisual) environments, and the realism of lighting effects (e.g., the occurrence or absence of shadows). Results indicated that effects of different manipulations of immersion are heterogeneous, affecting memory in some instances and presence in others, but not necessarily both. Importantly, no evidence for a mediating effect of presence emerged in any of these experiments, nor in a combined cross-experimental analysis. This outcome demonstrates a degree of independence between immersion and presence with regard to their influence on episodic memory performance.